VD_FINDINFO HC / 2024 / 1003 vom 22. Januar 2025 - VD Tribunal cantonal (2025)
MESURE PROVISIONNELLE, GARDE DE FAIT, RELATIONS PERSONNELLES, ÉCOLE, MODIFICATIONEN GÉNÉRAL, TÉMOIN, AUDITION DE L'ENFANT | 273 al. 1 CC, 298d al. 2 CC, 157 CPC (CH), 168 CPC (CH), 298 al. 1 CPC (CH)